T Cell-Mediated Modulation of Mast Cell Function: Heterotypic Adhesion-Induced Stimulatory or Inhibitory Effects - Mekori, Yoseph A.; Hershko, Alon Y. (Frontiers in Immunology, 2012)
Close physical proximity between mast cells and T cells has been demonstrated in several T cell mediated inflammatory processes such as rheumatoid arthritis and sarcoidosis. However, the way by which mast cells are activated in these T cell-mediated immune responses has not been fully elucidated. We have identified and characterized a novel mast cell activation pathway initiated by physical contact with activated T cells, and showed that this pathway is associated with degranulation and cytokine release. The signaling events associated with this pathway of mast cell activation have also been elucidated confirming the activation of the Ras MAPK systems. More recently, we hypothesized and demonstrated that mast cells may also be activated by microparticles released from activated T cells that are considered as miniature version of a cell. By extension, microparticles might affect the activity of mast cells, which are usually not in direct contact with T cells at the inflammatory site. Recent works have also focused on the effects of regulatory T cells on mast cells. These reports highlighted the importance of the cytokines IL-2 and IL-9, produced by mast cells and T cells, respectively, in obtaining optimal immune suppression. Finally, physical contact, associated by OX40-OX40L engagement has been found to underlie the down-regulatory effects exerted by regulatory T cells on mast cell function.